Employment insurance perspective on islamic law and job creation law No. 11 of 2020 on manpower No. 13 of 2003 - Ritonga, Ali Ummar (Islamic perspective on Communication and Psychology, 2024)
Background: The study of insurance within the framework of Islamic law is a relatively recent development, lacking representation in classical fiqh literature. Discussions surrounding insurance have emerged primarily with contemporary scholars, highlighting its importance in modern financial management. Today, insurance serves as a critical tool for financial planning, aimed at eliminating, avoiding, and minimizing potential risks that individuals and businesses may face. Methods: This research employs a qualitative approach, utilizing a case study methodology. The author gathered primary and secondary data through various field research methods, including observations, direct interviews, documentation, and library research. To address the research questions, the analysis is grounded in the theory of law implementation, focusing on the values of justice and legal certainty to achieve meaningful outcomes in practice. Findings: The findings reveal that, from an Islamic law perspective, conventional insurance cannot be classified as Islamic insurance due to its non-compliance with key characteristics and its inclusion of elements such as gharar (uncertainty), maysir (gambling), and usury. In contrast, Islamic insurance is defined by five fundamental characteristics: it is based on the principle of cooperation (tabarru'), aims to mitigate the impact of potential risks, features a membership association representing its members, ensures that insurance funds and investment returns remain the property of the members, and positions the insurance company as a service provider managing the funds. These characteristics are documented in the DSN-MUI fatwas concerning insurance. Conclusion: Despite these insights, the legal objectives intended by Islamic law and Law No. 13 of 2003 concerning manpower have not been fully realized. The core values of justice, legal certainty, and the benefits of the law remain inadequately achieved. The author argues that the existence of multiple regulatory frameworks governing employment insurance leads to legal dualism, resulting in a lack of clear legal certainty in employment insurance regulations. Novelty/Originality of this article: This article contributes to the understanding of Islamic insurance by clarifying the distinctions between conventional and Islamic insurance practices, emphasizing the need for clear regulations. It addresses the contemporary challenges faced in aligning legal frameworks with the principles of Islamic law, paving the way for further discussions and developments in the field of Islamic financial management.